Discrimination on the grounds of pregnancy, denial of maternity leave and lack of conducive environment for nursing mother in the workplace in South Africa - Matotoka, Motlhatlego D (Obiter, 2020)
In South Africa, women continue to be discriminated against on the grounds of being pregnant in the workplace and sometimes they are denied maternity leave, breastfeeding and childcare facilities. Methodologically, using a descriptive and content analysis research approach, this article examines how the apartheid era restricted the rights of pregnant women in the workplace, particularly black African women. Post-1994 South Africa, the article utilised various protective transformative legal and policy interventions that have been introduced and are being implemented to address the problem of discrimination against women on the grounds of pregnancy in the workplace.